Value of Matrix metalloproteinase-7and ‎Vimentin as Prognostic Biomarkers in Adenoid ‎Cystic Carcinoma (Immunohistochemical Study)‎ (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Background: matrix metalloproteinase-7 (MMP7), its primary role is to break down extracellular matrix including casein, type I, II, IV, and V gelatins, fibronectin, and proteoglycan. The upregulation of MMP7 is associated with many malignant tumors. Vimentin (Vim) plays an important role in malignant tumors with regard to cellular adhesion, migration and signaling. In our current study, we have attempted to evaluate the expression of MMP7 and Vim as markers for aggressive biological behavior of AdCC.  Materials and Methods: Nineteen formalin fixed paraffin embedded blocks of AdCC were collected retrospectively were included in this study. An immunohistochemical (IHC) staining was performed using anti MMP7 and anti Vim monoclonal antibodies. Results: MMP7 showed significant relation with larger size tumor (P=0.003), higher grade (P=0.006). The Vim was significantly correlated with minor salivary gland (P=0.041), larger size tumor (P=0.021), high grade (P=0.040).   Both markers revealed highly significant correlation with advanced stage (P